How to build an innovation ecosystem in enterprises -- taking 3nod as an example - LIU, Zhixiong (Institutional Knowledge at Singapore Management University, 2022)
In recent years, the global economy has been sluggish, especially affected by the Sino-USA trade war and the COVID-19, the harsh market environment and increased business uncertainty. In addition, China’s manufacturing industry is facing the impact of disappearance of the demographic dividend and strict environmental protection policies, so they are facing tremendous pressure for survival. At the same time, a new generation of science and technology continues to sprout and gradually penetrates in to production and life. Therefore, under these conditions, the innovation activities of manufacturing enterprises are more important and urgent. How to construct systematic innovation activities for manufacturing enterprises is a basic problem that cannot be avoided. Therefore, the research in this dissertation focuses on how core firms build enterprise innovation ecosystems based on technological and non-technological innovation and other multi-dimensional innovation management elements.Based on the micro perspective of the core firm in the enterprise innovation ecosystem, this dissertation first sorts out the definition of the core enterprise concepts in the enterprise innovation ecosystem. On this basis, from the different dimensions of enterprise innovation management, it carries out anexploratory single-case study of the corporate innovation ecosystem constructed by the famous domestic enterprise 3nod Group.Through the coding and analysis of the qualitative materials of realization nodes for the five innovative ecological unit of the unique OPM model of 3nod, this dissertation summarizes as follows: (1) Based on the external macro innovation environment, the core firm takes the user as the core, builds an innovation platform, and uses the technology synergy connection mechanism to establish different levels of cooperation relationship with technical resources parties and build an enterprise technology innovation ecosystem; at the same time, relying on the non-technical innovation peripheral support system with strategic innovation as the blueprint, cultural innovation as the guide, management innovation as the foundation, organizational innovation as the guarantee ,institutional innovation as the driving force and market innovation as the pathway, the core firm and related partners jointly establish an enterprise innovation ecosystem. (2) The core firm must effectively integrate the innovation management elements of technology, strategy, management, culture, organization, system, and market, so as to form a dynamic relationship with each other, and realize the continuous interaction between enterprises and users; and through build an innovation platforming, a fast and effective cooperation mechanism can be built between core enterprises and technical resource parties, the allocation of innovation resources within the system can be optimized , and mutual promotion and co-evolution among members in system can be realized .The research conclusions of this dissertation supplement and expand the existing theories of enterprise innovation ecosystems, and provide referencesfor innovation enterprises that are exploring the practice of constructing enterprise innovation ecosystems with themselves as the core.